2015
DOI: 10.18052/www.scipress.com/ilcpa.62.29
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Terahertz Time-Domain Spectroscopy of Archaeological Baltic Amber

Abstract: Abstract. We performed the broadband terahertz time-domain spectroscopy on archaeological Baltic amber at 40 million years old. We determined the real and imaginary parts of the complex dielectric constants in the frequency range from 0.2 to 6.5 THz. The imaginary part of the complex dielectric constants showed a broad peak at 1.51 THz and a small peak at 4.0 THz. A boson peak, which is the characteristic low energy excitation of a glassy state, was not observed above 0.2 THz even in low temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…In addition, the spectral data of Sasaki et. al [ 28 ] is shown. The Baltic amber spectral data from the present work qualitatively agrees very well with the previous results of Sasaki over the datasets common spectral range.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…In addition, the spectral data of Sasaki et. al [ 28 ] is shown. The Baltic amber spectral data from the present work qualitatively agrees very well with the previous results of Sasaki over the datasets common spectral range.…”
Section: Resultsmentioning
confidence: 94%
“…(e) Wyoming and Baltic amber: WY01_A (black lines) and BA-A (dark gray lines) amber samples. The spectral data of Sasaki et al Baltic data [ 28 ] are shown in light gray.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…intra-molecular as well as inter-molecular [6]. Schiff's bases are widely studied and used in the fields of organic synthesis and metal ion complexation [7] for a number of reasons: their physiological and pharmacological activities [8] their use in ionselective electrodes [9] in the determination of heavy metals ions in environmental samples [10] and in the extraction of metals ions [11,12] and their many catalytic applications (e.g. for epoxidation of olefins, alkene cyclopropanation [13,14] trimethylsilylcyanation of ketones [15] asymmetric oxidation of methyl phenyl sulfide enantioselective epoxidation of silylenol [16] and ring-opening polymerization of lactide [17].…”
mentioning
confidence: 99%